2022
DOI: 10.3389/fimmu.2022.1057980
|View full text |Cite
|
Sign up to set email alerts
|

CARMA3: A potential therapeutic target in non-cancer diseases

Abstract: Caspase recruitment domain and membrane-associated guanylate kinase-like protein 3 (CARMA3) is a scaffold protein widely expressed in non-hematopoietic cells. It is encoded by the caspase recruitment domain protein 10 (CARD10) gene. CARMA3 can form a CARMA3-BCL10-MALT1 complex by recruiting B cell lymphoma 10 (BCL10) and mucosa-​associated lymphoid tissue lymphoma translocation protein 1 (MALT1), thereby activating nuclear factor-​κB (NF-κB), a key transcription factor that involves in various biological respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…In this study, it was found that blood MALT1 was positively correlated with BMI and PASI score in psoriasis patients. Regarding BMI, it could be explained by that MALT1 might form a complex with BCL10 and CARD3 to regulate insulin resistance, leading to an increase in BMI 24,25 . With respect to the PASI score, MALT1 could facilitate Th17 cell and γδ T17 cell differentiation, inflammatory cytokine (such as TNF‐α, interleukin [IL]−17A, and IL‐1β) production, and keratinocyte proliferation to eventually lead to psoriasis symptoms, including hyperkeratosis of the epidermal tissue, loss of the granular layer and epidermal microabscesses, contributing to a higher PASI score 14–16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, it was found that blood MALT1 was positively correlated with BMI and PASI score in psoriasis patients. Regarding BMI, it could be explained by that MALT1 might form a complex with BCL10 and CARD3 to regulate insulin resistance, leading to an increase in BMI 24,25 . With respect to the PASI score, MALT1 could facilitate Th17 cell and γδ T17 cell differentiation, inflammatory cytokine (such as TNF‐α, interleukin [IL]−17A, and IL‐1β) production, and keratinocyte proliferation to eventually lead to psoriasis symptoms, including hyperkeratosis of the epidermal tissue, loss of the granular layer and epidermal microabscesses, contributing to a higher PASI score 14–16 …”
Section: Discussionmentioning
confidence: 99%
“…Regarding BMI, it could be explained by that MALT1 might form a complex with BCL10 and CARD3 to regulate insulin resistance, leading to an increase in BMI. 24,25 With respect to the PASI score, MALT1 could facilitate Th17 cell and γδ T17 cell differentiation, inflammatory cytokine (such as TNF-α, interleukin [IL]−17A, and IL-1β) production, and keratinocyte proliferation to eventually lead to psoriasis symptoms, including hyperkeratosis of the epidermal tissue, loss of the granular layer and epidermal microabscesses, contributing to a higher PASI score. [14][15][16] Systemic biologic therapy has recently received a lot of attention due to its rapid onset of action, safety, and ability to target specific immune system-mediated inflammatory cytokines to attenuate psoriasis activity.…”
Section: Correlation Of Blood Malt1 With Psai 75 and 90 At M6 In Psor...mentioning
confidence: 99%
“…Since so many POAG-associated CARD10 mutants did not show any signs of activation, we would expect other phenotypes in addition to POAG in this model. The activated Card10 knock-in mouse model could thus also provide a valuable novel model to investigate the effects of hyperactive CARD10 in other diseases, such as cancer, asthma, liver- and lung fibrosis [101]–[104]. Some additional Genebass [57] associations for this natural CARD10 R212H variant (22-37516037-C-T; allergy, arthritis, cardiovascular disease, cancer), which partially overlap with the phenotypes associated to the MALT1 cleavage resistant CARD10 R587 variants, indicate that such phenotypes may be likely.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the stronger activated artificial mutant Card10 G128D or Card10 L132P knock-in mice would be interesting to generate in order to specifically look at the physiological effects of CARD10 activation without the potential additional off-target association to POAG. The activated Card10 knock-in mouse model could thus also provide a valuable novel model to investigate the effects of hyperactive CARD10 in other diseases, such as cancer, asthma, liver- and lung fibrosis [98101]. Some additional Genebass [63] associations for this natural CARD10 R212H variant indicate that such phenotypes may be likely.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the stronger activated artificial mutant Card10 G128D or Card10 L132P knock-in mice would be interesting to generate in order to specifically look at the physiological effects of CARD10 activation without the potential additional off-target association to POAG. The activated Card10 knock-in mouse model could thus also provide a valuable novel model to investigate the effects of hyperactive CARD10 in other diseases, such as cancer, asthma, liver-and lung fibrosis [98][99][100][101]. Some additional Genebass [63] associations for this natural CARD10 R212H variant indicate that such phenotypes may be likely.…”
Section: Discussionmentioning
confidence: 99%